Disentangling the effects of methanogen community and environment on peatland greenhouse gas production by a reciprocal transplant experiment. (12th February 2020) - Juottonen, Heli
Abstract: Northern peatlands consist of a mosaic of peatland types that vary spatially and temporally and differ in their methane (CH4 ) production. Microbial community composition and environment both potentially control the processes that release carbon from anoxic peat either as CH4 or as carbon dioxide (CO2 ), a less potent greenhouse gas than CH4 . However, the respective roles of these controls remain unclear, which prevents incorporating microbes in the predictions of peatland CH4 emissions. Here, a reciprocal transplant experiment was carried out to separate the influences of microbial community and environment in CH4 and anaerobic CO2 production. Peat from an acidic Sphagnum bog and a sedge fen with higher pH was enclosed in membrane bags with a pore size of 0.2 µm, preventing microbial colonization from the outside, and transplanted in the field for 2 months. Potential CH4 production was primarily controlled by the environment. The conditions in the bog suppressed the initially higher activity of fen methanogens and reduced CH4 production by 79%. Against expectations, the inhibition was not specific to acetate‐using Methanotrichaceae. Reciprocal transplantation favoured Methanosarcinaceae and potentially methylotrophic methanogenesis in general. Bog methanogens, mostly hydrogenotrophic Methanoregulaceae, retained their community structure and activity in the fen with a slight increase (+37%) in CH4 production. Anaerobic CO2 production was controlled by both the microbial community and the environment. Transplantation led to increased CO2 production in both bog (+50%) and fen peat (+57%) with distinct bacterial community, showing that the new environment directed more carbon to other anaerobic processes than methanogenesis. Taken together, these results relate differences in CH4 production of bogs and fens to ecophysiology of specific methanogen groups. The sensitiveness of fen methanogens to the acidic conditions in Sphagnum bogs can help explain the decrease in CH4 emission in the typical boreal peatland succession from young fens to older bogs. Increase in anaerobic CO2 versus CH4 production with transplantation shows that disturbances of boreal peatlands can activate poorly defined pathways of anaerobic decomposition. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.